(untitled) (Fiep Bulletin - online, 2016)
The popularity of flag football in young players has increased as a fashion that provides a significant membership in this age to develop physical skills, sense of belonging and teamwork. The study aimed at promoting self control through reflective teaching to beginners players at flag football. To this end the following research questions were formulated: To what extent a reflective teaching flag football flag favors self control in competition? The sample was composed by 35 players between 15 and 20 years old, which trained for four months, five days a week for two hours. Reflective teaching was to bring together the players in the final stage of training and after each game, for 15 minutes to discuss individual performance, providing an opportunity for each player to recognize their emotional states, and propose suggestions on team handling difficult situations during the game and controlling anxiety before starting a competition. Emotional states before competing to identify the level of anxiety were evaluated; applied three times during the month (June, July and August 2014). Measurements were grouped into three blocks in three games, making a total of nine measurements. It was felt that after every three games could be changes in the emotional state of the players that could be related with the teaching-learning employee, emphasizing reflective practice of sport. Test Competitive State Anxiety Inventory (CSAI-2) was used. The hypothesis with increasing self control before a competition in which beginners players at the flag football, to participate in a thoughtful process of teaching and learning the basic principles are accepted.